Application of the contingent valuation method to the moroccan argan: Case of the Souss Massa National Park (PNSM) - Ilyass ARRAHMOUNI; Majid BENABDELLAH; Kenichi KASHIWAGI; Mohammed DEHHAOUI; Faiçal BENCHEKROUN (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2018)
One of the main challenges of the Argan value chain is the construction of a sustainable project for the development of the sector and its products while protecting the Argan tree. The Souss Massa National Park can play an important role in this direction, through the promotion of ecotourism aimed at protecting and preserving Argan heritage. In this context, this work aims to estimate the willingness to pay to visit the Park and protect the argan tree, in the perspective that their payment will be dedicated to the protection of the argan tree. Using the contingent valuation method, this study shows that visitors are willing to pay (WTP) for the services of the proposed circuit. According to the Logit model, the results of this survey give an average value of WTP ranging from 37,598 Dhs as estimate at the level of the province of Tiznit to 76,985 Dhs as web estimation. On the other hand, according to the Probit model, this estimate varies between 55,129 Dhs and 85,031 Dhs. Assuming a number of visits ranging from a pessimistic scenario of 100,000 visitors to more optimistic scenario of 300,000 visitors, the public authorities can collect between 3.8 Mdhs to 26.8°Mdhs/year by establishing this willingness to pay as a fee to enter in the park. Based on the survey conducted at province of Tiznit, Tobit modeling was allowed to evaluate the determining factors of willingness to pay. The age factor had a negative impact on willingness to pay, while revenues, distance from the park and ecological fiber had positive effects. On the other hand, the web survey identified different significant variables such as nationality, marital status, educational level, household size, income and knowledge of the park.